Legal Protection for the Customary Law Community of the Amungme Tribe Whose Land is Affected by Mining Activities by PT Freeport Indonesia - Panjaitan, Rudy (Universitas Pelita Harapan, 2025)
Protection of the unity of customary law communities to defend their constitutional rights if there is a law that is detrimental to their constitutional rights is enshrined in Law Number 24 of 2003 on Constitutional Court juncto Law Number 8 of 2011 on Amendments to Law Number 24 of 2003. The purpose of this research is to analyze legal protection for customary law communities over their customary land rights in the mining area, the implementation of the customary rights of the Amungme tribal customary law community in Papua on which there is gold mining carried out by PT Freeport Indonesia, and the ideal legal politics for customary law communities whose customary lands are affected by mining. The research method used in this study is normative juridical. The unclear boundaries of recognition become a potential conflict (dispute) against the existence of the position of customary rights over land today in Papua Province, which have a diversity of customary law communities (tribes/clans/clans) spread based on the ecology of highland culture (mountainous, pre-mountainous, and lowland areas) in Papua. Customary law communities are allowed to deal directly with mining entrepreneurs who will use customary land for their mining business activities. The need for the formation of associations such as in mining, such as in Lihir Papua New Guinea, will provide legal certainty and maximum benefits for the Amungme customary law community